Growth performance and survival rate of striped eel catfish (Plotosus lineatus) in the domestication (Biodiversitas Journal of Biological Diversity, 2021)
Asriyana, Halili, Hamzah M, Kurnia A. 2021. Growth performance and survival rate of striped eel catfish (Plotosus lineatus) in the domestication. Biodiversitas 22: 5593-5599. The striped eel catfish, Plotosus lineatus, is one of the catfishes that live in coral reefs and have high economic value. The fish is available in the wild and can be domesticated to supply animal protein necessity. This study aims to determine the optimum catfish size that would support their domestication process based on growth performance and survival rate in controlled media. The catfish's total length and body weight were measured every two weeks within the 56 days of rearing. The experiment was conducted with a completely randomized design composed of three treatment groups (based on fish length size) and four replications, namely 3.5-4.0 cm (group A), 4.9-5.6 cm (group B), and 7.0-8.0 cm (group C) with a density of five fish per pond. Results indicated that the catfish could live in a saline water pond. The growth performance of treatment group B was higher than treatment group A and C with absolute length growth (Lm) values of 2.19±0.63 cm, the daily growth rate in length (DGRL) of 0.04±0.05 cm/day, relative growth rate (RGR) of 0.51±0.58%/day, and specific growth rate of (SGR) 1.63±0.74%/day. However, the highest survival rate was observed in the treatment C group (65.00±4.08%), followed by treatment group A (46.25±2.50) and B (31.00±7.42). These findings will assist in the domestication of striped eel catfish to support the conservation of striped catfish populations in the future.
Keywords: Domestication, growth, Plotosidae, Plotosus lineatus, restocking